(untitled) (GEOgraphia, 2009)
Resumo As práticas espaciais são a base da organização geográfica das sociedades. O resultado da acumulação dessas práticas espaciais é um tecido espacial cada vez mais denso, móvel, fluido e liso, que determina a estrutura geográfica complexa que a sociedade vai adquirindo no tempo. Palavras-chaves: Práticas Espaciais. Construção das Sociedades. Re-estruturação espacial. Abstract Summary:The spatial practices are the basis of geographic organization of societies. The result of the accumulation of this spatial practices is a spatial tissue successively more dense, movable, fluid and smooth that determines the complex geographic structure of the society in time. Keywords: Spatial Practices. Society Construction. Spatial Re-structuration.